1999
DOI: 10.1002/(sici)1521-3773(19990517)38:10<1452::aid-anie1452>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Two New Modes of Pd-Catalyzed Domino-Tetracyclization of Bromodienynes—5-exo-trig Cyclization Wins overβ-Hydride Elimination

Abstract: Remarkable increases of molecular complexity in a single procedural step are achieved with the title reaction. Only a slight modification in the substitution pattern on the acyclic precursor 2 can change the mode of tetracyclization to either yield skeletons of type 1 or 3 exclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 2 publications
(4 reference statements)
0
22
0
Order By: Relevance
“…The Mizoroki‐Heck reaction has played a pivotal role in the synthesis of an immense array of industrially and pharmaceutically important compounds . Mechanistically, the Heck reaction proceeds through the formation of an alkyl‐Pd complex and subsequent β‐hydride elimination which is the key step in determining the selectivity between Mizoroki‐Heck product vs 1,4‐addition product (known as reductive Heck product), tuned by presence/absence of the external hydride source . In 1980s, Cacchi et al .…”
Section: Introductionmentioning
confidence: 99%
“…The Mizoroki‐Heck reaction has played a pivotal role in the synthesis of an immense array of industrially and pharmaceutically important compounds . Mechanistically, the Heck reaction proceeds through the formation of an alkyl‐Pd complex and subsequent β‐hydride elimination which is the key step in determining the selectivity between Mizoroki‐Heck product vs 1,4‐addition product (known as reductive Heck product), tuned by presence/absence of the external hydride source . In 1980s, Cacchi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al [99] and de Meijere and Co-workers [100] reported palladium-catalyzed cyclization reactions in which cyclizations are preferred over the b-elimination routes.…”
Section: Other Methods Of Suppressing the B-hydride Eliminationmentioning
confidence: 99%
“…The reaction required 2,2‐disubstituted terminal olefins so that in situ‐generated C(sp 3 )‐PdX species would contain no β‐H. A similar Pd‐catalyzed cascade cyclization was also reported by de Meijere and coworkers in which four 6/5/6/3‐membered rings were generated sequentially in one step (Scheme ) …”
Section: Dicarbofunctionalization Of Tethered Olefins Involving Cyclimentioning
confidence: 99%